Reservoir Potential of Neogene Rocks in the Biak Island and Its Surrounding Areas - Alviyanda Alviyanda; G.M. Lucki Junursyah; Rahmat Saragih (Berita Sedimentologi, 2019)
Biak Basin is located offshore to the immediate west and southwest of Biak Island. The basin contains up to 7,000m thick of sediments, which may be thermally mature to generate hydrocarbon if source rocks are present. The stratigraphy of the Biak Basin is generally dominated by carbonate sequences of Early to Late Neogene. The basin was drowned during the Oligocene, which could have led to source rock accumulation during this period. Then, carbonate platform facies were deposited massively above and can be of potential reservoir. The Neogene carbonates consist of two depositional sequences, namely Early Neogene sequence that contains Wainukendi, Wafordori, and Napisendi Formations; and Late Neogene sequence that contains Korem and Wardo Formations. A Late Miocene unconformity separates the two carbonate sequences.Reservoir rock potential of the Neogene carbonates has been evaluated by using quantitative parameters. Based on the evaluation, grainstone interbedded crystal limestone from the Napisendi Fm members has porosity ranging from 8.84% – 29.5% which can be categorized as good to special. Porosity types of the rock vary from intercrystalline, intracrystalline, and fracturing to vuggy. Secondary porosity occurred due to diagenetic rocks processes such as compacting, cementing, dissolution and dolomitization.